Post-Graduate Course in Selection and Management with Antimicrobial in Respiratory and Urinary Infections - Diana Rosa Fernández Ruiz; Maira Quiros Enríquez; Olga Lidia Cuevas Pérez; Eidys Rodríguez Herrera; Myriam Damaris Padilla Labrado (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Background: one of the pharmacologic groups of bigger prescription and use in Primary Health Attention, for his efficacy in the treatment of multiple infections constitute the antimicrobial. Previous studies evidence that there are difficulties in their prescription by doctors of this level of attention. Objective: designing a post-graduate course about the suitable selection and management of the antimicrobial in respiratory and urinary infections in primary health attention. Methods: a descriptive study, accomplished at the University of Medical Sciences of Cienfuegos, shaped for three stages: diagnosis of the level of knowledge taking as sample 113 comprehensive general doctors of all the health areas of Cienfuegos; the course's design, and its validation by consulting experts. They were considered the recommendations of the guides and protocols with the best available scientific evidences about the theme. Results: the majority of the inquired individuals presented a level of knowledge between middle and low about the theme. The course was structured in five themes, with its respective objectives, organizational teaching forms, methodological guidelines, methods and teaching aids. The experts validated the course and considered it feasible, pertinent and of lofty quality. Conclusions: the course can contribute to the increment of doctor's knowledge of the family about a selection and management of antimicrobial in the most frequent infections in Primary Health Attention, and therefore, to upgrade medical attention to the patient.